II.–The Diagrammatical Representation - Lerner, A. P. (Review of Economic Studies, 1933)
II.—The Diagrammatical Representation Get access A. P. Lerner A. P. Lerner London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 1, October 1933, Pages 68–71, https://doi.org/10.2307/2967440 Published: 01 October 1933